KEKURANGAN ZAT BESI DI PEREMPUAN HAMIL MENGGUNAKAN HEMOGLOBIN RETIKULOSIT (RET-HE) - Petriana Primiastanti; Ninik Sukartini (Indonesian Association of Clinical Pathologist and Medical laboratory, 2013)
Iron deficiency is the most common nutrional deficiency in the world, mostly in developing and industrial countries. Population with highest risk of iron deficiency generally are reproductive-age women. In Indonesia, the prevalence of iron deficiency anemia in pregnant women is about 50.5%. Anemia due to iron deficiency in pregnancy can affect both mother as well as the foetus. In order to prevent permanent systemic complication, it is important to do early detection before iron deficiency anaemia developes. In the early phase of iron deficiency prior to anaemia, additional tests of ferritin, serum iron and saturation index are needed besides the complete blood count. A new parameter named reticulocyte hemoglobin equivalent (RET-He) has been developed to detect the level of hemoglobin in an immature erythrocyte or reticulocyte. Reticulocytes will be present in the peripheral circulation for only 24−48 hours, so the RET-He will give more appropriate information about the condition of bone marrow iron. When the bone marrow iron is depleted, the RET-He will show a decrease. In several hematology analyzers, for example Advia 2120 and Sysmex XE 2100, this parameter can be tested together with CBC, so no additional blood sample is needed. The aim of this study is to know iron deficiency in healthy first and second trimester pregnant women by screening using RET-He and compare the result to other parameters that are now available, such as: hemoglobin, ferritin, transferrin saturation. Those parameters can develop RET-He cut-off with optimal sensitivity and specificity. The study comprised 100 healthy pregnant women from I and II trimester who did not develop anemia yet during their last pregnancy. The subjects were divided into three (3) groups based on ferritin and transferrin saturation: 67 women (67%) without iron deficiency, 17 women (17%) with iron deficiency stage I, and 16 women (16%) with iron deficiency stage II. Hemoglobin, RET-He, and transferrin saturation showed a mean±SD of 12.35±1.02 g/dL, 33.60±1.88 pg and 28.63±1.07%, respectively. Median ferritin (min-max) was 40.10 (6.24–191.30)ng/mL. By using receiver operating curve (ROC) in this study RET-He point was found at 33.65 pg as an optimal cut-off point to differentiate iron deficiency with sensitivity and specificity of 67% and 64.18% respectively. From cross tabs table of RET-He with ferritin as the gold standard and 33.65 pg as the cut-off point results were 47.8% positive predictive value (PPV), 79.6% negative predictive value (NPV), positive likelihood ratio (LR) 1.86 and negative likelihood ratio (LR) 0.52. In this study, significant differences between non iron deficiency and the iron deficiency stage II groups and between iron deficiency stage I and iron deficiency stage II groups were found. There was no difference between the non iron deficiency and iron deficiency stage I groups.